Building Back Wards in a 'Post' Institutional Era: Hospital Confinement, Group Home Eviction, and Ontario's Treatment of People Labelled with Intellectual Disabilities - Spagnuolo, Natalie (Disability Studies Quarterly, 2016)
Although Ontario has closed the regional centres that were intended for people labelled with intellectual disabilities and apologized to survivors, the institutionalization of disabled people persists in other forms in the province. This article demonstrates that the eligibility criteria established by privately-operated and publically-funded group homes contributes to the use of what will be termed 'back ward' placements in institutions such as hospitals and nursing homes. While group homes themselves have been – quite rightly – criticized as neo-institutional forms of residential support, they also play a role in shaping more overt forms of confinement by refusing to tailor their services to the needs of certain individuals. What follows is an analysis of residential support systems that builds upon case studies and reports to expose how impairment hierarchies, based on ranked support needs, determine who will end up in these 'back wards' and who will be offered a place in a group home.